Morphological characterization ofMadura Cattle - Bambang Setiadi; Kusuma Diwyanto (Jurnal Ilmu Ternak dan Veteriner, 1998)
Morphological characterization of Madura cattle in Madura islands was done as an input for "action plans" of national animals genetic resources management according to the global system ofFAO. Assessments were done in Sumenep District and Pamekasan District, East Java. According to the body measurements, Madura cattle can be classified as a small to medium type with withers height of about 120 cm. Because of potential productivity in the limitation of environmental resources, Madura cattle can be classified as a "superior" cattle . Body measurements of Madura cattle in the present study were relatively the same with those of 50 years ago, indicating that there is no breeding improvement activities except natural selection . The variability of body measurements is relatively narrow . Improving productivity by outbreeding is needed . To conserve the unique germ plasm of the Indonesian genotype, such as Madura cattle and a possibility to improve their productivity by a complete prevention of cross breeding in the Madura islands needs further evaluation .   Keywords: Madura cattle, morphological characteristic, conservation